The Legal Protection of Cinematographic Works in The Digital Era: A Case Study on Film Piracy via Unauthorized Streaming Platforms - Nadita Oktaviona; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2025)
In the digital age, the act of watching films through digital streaming platforms has emerged as a new distribution method for Indonesian filmmakers, who continue to evolve and thrive within the film industry. This study aims to examine the legal responsibilities associated with the rise of film piracy on illegal platforms and the measures taken to protect cinematic copyrights in such environments. This research employs a normative legal method, focusing on the internal aspects of positive law through a descriptive approach to provide an objective summary. The analysis is conducted qualitatively by examining secondary data sources, utilizing a literature review method relevant to the issues at hand. Law of the Republic of Indonesia Number 28 of 2014 concerning Copyright provides protection for intellectual property rights; however, this legal framework has not deterred individuals from engaging in film piracy. Although access to illegal streaming websites has been blocked, such platforms continue to proliferate in line with technological advancements. Both litigation and non-litigation measures have been implemented by the government to safeguard the rights of creators and to impose a deterrent effect on violators.